Application of power law in shallow open channel flows - Tan, Jian Ming. (2011)
The knowledge of rough bed flow is essential for open channel hydraulics as flow in rivers can be considered as hydraulically rough and channel morphology and local bed friction are major contributors to flow resistance.Many researches were conducted for open channel flow with large relative submergence but few researches were conducted for flow with low relative submergence in an open channel. The hydraulics of shallow open channel flow is therefore poorly understood.